PENGARUH ELECTRONIC WORD OF MOUTH, PROMOSI PRODUK DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA APLIKASI SHOPEE - Noval Freksi MP; Tezar Arianto (Yayasan Insani Mandiri Santani, 2023)
This study expects to decide the impact of Electronic Word of Mouth, Promotion, and Brands on Purchase Decisions for Shopee Customers in Bengkulu City. This exploration was directed on Shopee clients in Bengkulu City. The populace utilized in this study were Shopee clients in Bengkulu City. The quantity of tests utilized was 105 respondents. The information that has been gathered is handled utilizing the Classical Assumption Test Technique, Multiple Linear Regression Analysis Technique, Coefficient of Determination Analysis (R2), and Partial Test (t-test), Simultaneous Test (f-test). The consequences of this study show that somewhat the Electronic Word of Mouth variable significantly affects the Purchase Decision variable, H1 is acknowledged, Promotion significantly affects the Purchase Decision variable, H2 and Brand significantly affect the Purchase Decision variable, H3 is acknowledged. While the f-trial of Electronic Word of Mouth (X1), Promotion (X2) and Brand (X3) impact Purchase Decisions (Y) of Bengkulu City Shopee clients with the goal that H4 is acknowledged. The generally critical level is (sig = 0.000 < 0.05). Furthermore, has a relapse condition Y = 0.316 + 0.1255X1 + 0.336X2 + 0.671X3. Where the relapse condition implies that together the Electronic Word of Mouth, Promotion and brand factors show that every factor has a relationship with Purchase Decisions for Shopee Customers in Bengkulu City. Keywords: Electronic Word of Mouth, Promotion, Brand, Purchase Decision